Pendidikan Kesehatan Melalui Media Video dan Komik untuk Pencegahan Anemia pada Remaja Putri - Yuanita Syaiful; Lilis Fatmawati; Sheintia Prihastuti (LPPM UNIVERSITAS DIAN NUSWANTORO, 2022)
Anemia is a major health problem in adolescent girls. The provision of health education through video and comic media is an alternative to improve behavior. Adolescents who are members of the IPNU of Leran Manyar Gresik Village have less knowledge so that they affect attitudes and actions to prevent anemia. The village midwife has tried to provide counseling about anemia through lectures but the results have not been efficient, the young women have not heeded the problem of nutritional intake. So that adolescent health problems are quite a big problem. Therefore, it takes health education to prevent anemia in adolescent girls with other methods, namely the comic and video method. This service aims to increase the knowledge, attitudes and actions of young women to eat nutritiously so that they can increase nutritional intake during pregnancy and prevent anemia. The method used is to provide health education through comics and videos, and to provide questionnaires. Questionnaires were given on day 1 (pre test) and day 4 (post test) to 28 young women by complying with the health protocol. The results of the questionnaire were used to determine the understanding of young women about anemia prevention until there was a change in attitudes and actions as an indicator of the success of the activity. Health education was delivered through the provision of comics and video screenings (±30 minutes) about anemia prevention in 3 meetings with material on the definition of anemia, its impact on adolescents, and how to prevent it. The results showed that there was an increase in knowledge from less (85.7%) to good (100%), attitude from negative to 100% positive, less action (71.4%) to good (100%). Based on these results, it is expected that adolescents can apply the knowledge, attitudes and actions correctly to achieve the highest health status in adolescents.